CO2 capture with solid sorbent: CFD model of an innovative reactor concept. (15th January 2016) - Barelli, L.; Bidini, G.; Gallorini, F.
Highlights: A new reactor solution based on rotating fixed beds was presented. The preliminary design of the reactor was approached. A CFD model of the reactor, including CO2 capture kinetic, was developed. The CFD model is validated with experimental results. Sorbent exploitation increasing is possible thanks to the new reactor. Abstract: In future decarbonization scenarios, CCS with particular reference to post-combustion technologies will be an important option also for energy intensive industries. Nevertheless, today CCS systems are rarely installed due to high energy and cost penalties of current technology based on chemical scrubbing with amine solvent. Therefore, innovative solutions based on new/optimized solvents, sorbents, membranes and new process designs, are R&D priorities. Regarding the CO2 capture through solid sorbents, a new reactor solution based on rotating fixed beds is presented in this paper. In order to design the innovative system, a suitable CFD model was developed considering also the kinetic capture process. The model was validated with experimental results obtained by the authors in previous research activities, showing a potential reduction of energy penalties respect to current technologies. In the future, the model will be used to identify the control logic of the innovative reactor in order to verify improvements in terms of sorbent exploitation and reduction of system energy consumption.